Organoleptic and Nutritional Content of Cookies With Mackerel Flour and Tempeh Flour Substitutions for Children With Protein-Energy Malnutrition - Maria Betsie Wezendonk; Astuti Nur (Saintify Publish, 2025)
According to the BB/U indicator, 7.3% of toddlers suffer from malnutrition and 22.2% from undernutrition in East Nusa Tenggara. This study aimed to determine the organoleptic properties of cookies with mackerel flour and tempeh flour substitutions for children with energy protein deficiency. This experimental research was conducted using a Completely Randomized Design with substitutions of mackerel fish flour and tempeh flour. P0 no substitution, P1 25%: 5%, P2 35%: 15%, P3 45%: 25%. Based on the Kruskal-Wallis test, there was an effect of the substitution of mackerel flour and tempeh flour on the color of cookies with a P-value of 0.002. Further testing using the Mann-Whitney test showed that the significantly different formulas were P1 and P3. The most preferred treatment in terms of aroma was P1, with an average value of 3.9 (liked). Based on the Kruskal-Wallis test, there was no effect of the substitution of mackerel flour and tempeh flour on the aroma of cookies with a P-value of 0.195. The most preferred treatment in terms of texture was P1, with an average value of 4.06 (liked). Based on the Kruskal-Wallis test, there was no effect of the substitution of mackerel flour and tempeh flour on the texture of cookies, with a P-value of 0.100. The most preferred treatment in terms of taste was P1, with an average value of 4.03 (liked). Based on the Kruskal-Wallis test, there was no effect of the substitution of mackerel flour and tempeh flour on the taste of cookies with a P-value of 0.142. The conclusion for the organoleptic test, the variance test for taste, aroma, texture, and flavour of cookies with mackerel flour and tempeh flour substitutions, showed that panellists preferred product P1 to products P2 and P3.